PENGARUH PENDIDIKAN KESEHATAN FISIK TERHADAP KUALITAS HIDUP PADA PEREMPUAN MENOPAUSE DI POSYANDU LANSIA BINA SEJAHTERA RW 05 BUKIT SANGKAL PALEMBANG - Lisda Maria; Cindy Agustina (LPPM STIKes Mitra Adiguna, 2026)
Menopause is a natural phase in a woman’s life characterized by decreased estrogen levels, affecting physical, psychological, social aspects, and overall quality of life. Limited knowledge and skills in managing physical changes during menopause may reduce women’s well-being. This study aimed to examine the impact of physical health education on the quality of life of menopausal women. A pre-experimental design with a one group pretest-posttest approach was used. The sample consisted of 30 menopausal women choosed through purposive sampling. The WHOQOL-OLD questionnaire was used to measure quality of life. Data were examined using the Paired Sample t-test after conducting the Shapiro-Wilk normality test. The outcomes presented a significant improvement in quality of life after the intervention, with a p-value < 0.001 (? = 0.05). Physical health education had a positive and significant effect on improving the quality of life of menopausal women. These findings highlight the importance of structured physical health education programs as promotive and preventive strategies to enhance menopausal women’s well-being.